Pakistan’s Afghan Policy: Securitized Identity and Ontological (In) Security - Nasrullah Khan; Sayed Wiqar Ali Shah, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Pakistan and Afghanistan are geographically contiguous and share same faith— factors that should have brought them close to each other. However, for most of the time relations between them have remained contentious. This paper is an effort to observe improved engagement with Pakistan’s Afghan policy through social constructivist’s reading of ontological (in)security. It also critically engages with the policy’s implications, reasons for the urge of an alternative and its possible future prospect. Policies adopted are “easy fixes” which has led to an increased securitization of identity hence deepening uncertainty. The only way out is desecuritization—transformation of identity towards a democratic self— followed by promoting shared meanings between the two. Methodologically, this study is based on a case study approach which is urged by case specificities that can be generalized to other cases.